2004
DOI: 10.1128/aem.70.10.6037-6046.2004
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Diversity of Microbial Communities Recovered from Surrogate Minerals Incubated in an Acidic Uranium-Contaminated Aquifer

Abstract: Our understanding of subsurface microbiology is hindered by the inaccessibility of this environment, particularly when the hydrogeologic medium is contaminated with toxic substances. In this study, surrogate geological media contained in a porous receptacle were incubated in a well within the saturated zone of a pristine region of an aquifer to capture populations from the extant communities. After an 8-week incubation, the media were recovered, and the microbial community that developed on each medium was com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
105
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(123 citation statements)
references
References 50 publications
(34 reference statements)
13
105
5
Order By: Relevance
“…Although previous studies have suggested that there may be significant differences in the microbial communities associated with sediments and groundwater in the subsurface (Pedersen and Ekendahl, 1990;Holm et al, 1992;Lehman et al, 2001Lehman et al, , 2004Reardon et al, 2004), it is not too surprising that major differences were not observed in the Geobacter-dominated samples from the Rifle study site. This is because recent studies have noted that although Geobacter species must directly contact Fe(III) oxides to reduce them (Nevin and Lovley, 2000), Geobacter species are also highly motile during growth on Fe(III) oxides (Childers et al, 2002).…”
Section: Discussionmentioning
confidence: 73%
“…Although previous studies have suggested that there may be significant differences in the microbial communities associated with sediments and groundwater in the subsurface (Pedersen and Ekendahl, 1990;Holm et al, 1992;Lehman et al, 2001Lehman et al, , 2004Reardon et al, 2004), it is not too surprising that major differences were not observed in the Geobacter-dominated samples from the Rifle study site. This is because recent studies have noted that although Geobacter species must directly contact Fe(III) oxides to reduce them (Nevin and Lovley, 2000), Geobacter species are also highly motile during growth on Fe(III) oxides (Childers et al, 2002).…”
Section: Discussionmentioning
confidence: 73%
“…There is some evidence for a reverse trend for archaea, which exhibited higher abundance and diversity in groundwater compared with sediment in one study (Flynn et al, 2013). In studies that directly compared sediment and groundwater communities from the same site, a trend of no more than 30% overlap in the bacterial communities was determined (Reardon et al, 2004;Flynn et al, 2008Flynn et al, , 2013. Gene surveys of 16 S rRNA provide, at best, species-level resolution, but most studies have focused on higher taxonomic levels, or, alternatively, tracked a few specific lineages of interest across samples (Reardon et al, 2004;Flynn et al, 2013;Longnecker & Kujawinski, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In studies that directly compared sediment and groundwater communities from the same site, a trend of no more than 30% overlap in the bacterial communities was determined (Reardon et al, 2004;Flynn et al, 2008Flynn et al, , 2013. Gene surveys of 16 S rRNA provide, at best, species-level resolution, but most studies have focused on higher taxonomic levels, or, alternatively, tracked a few specific lineages of interest across samples (Reardon et al, 2004;Flynn et al, 2013;Longnecker & Kujawinski, 2013). As an example, Flynn et al (2008) examined distributions of the metal-respiring microbes Geothrix and Geobacter, showing Geobacter sp.…”
Section: Introductionmentioning
confidence: 99%
“…Early research demonstrated that attached populations may exhibit distinct cell morphology ) and physiology (Köl-bel-Boelke & Hirsch 1989, Hirsch 1992, Watnick & Kolter 2000. More recently, it has been confirmed that suspended and attached prokaryotic communities most often show striking differences also in community composition (Reardon et al 2004, Flynn et al 2008, Griebler & Lueders 2009, Anneser et al 2010, Rizoulis et al 2013, Hug et al 2015. The factors responsible include those mentioned above as well as additional ones such as the chemical composition of the groundwater, substrate, and electron acceptor availability, the redox conditions and, explicitly, the impact of contaminants (Griebler & Lueders 2009, Rizoulis et al 2013).…”
Section: Introductionmentioning
confidence: 94%
“…Image: Christian Griebler & Clemens Karwautz subsequent composition of communities as well as the distribution of cells between the pore water and the solid phase (Reardon et al 2004, Fazi et al 2008, Kanzog & Ramette 2009, Augspurger et al 2010, Flynn et al 2013, Rizoulis et al 2013. In habitats poor in nutrients and/or organic carbon, sediment surfaces have frequently been suggested to be attractive habitats for microbes since they are offering access to limiting elements contained in the minerals (Banfield & Hamers 1997, Bennett et al 2000, 2001, Rogers & Bennett 2004, Boyd et al 2007, Mauck & Roberts 2007, Carson et al 2009, Gadd 2010.…”
Section: Introductionmentioning
confidence: 99%